(untitled) (Journal of Shaheed Suhrawardy Medical College, 2020)
Laparoscopic inguinal hernia repair has become popular as an alternative to open surgery. The classical TEP technique is the laparoscopic technique of hernia repair which is considered closest to ideal for inguinal hernia repair, but this technique has several drawbacks such as limited space for dissection and mesh placement, restricted port placement, a low tolerance of accidental pneumoperitoneum, and difficulty in teaching and learning the technique. Extendedview modification, the eTEP technique, which overcomes several of these drawbacks. The eTEP approach can quickly and easily create an extraperitoneal space, enlarge the surgical field, provide a flexible port setup adaptable to many situations, allow unencumbered parietalization of the cord structures , ease the management of the distal sac in cases of large inguinoscrotal hernias, and improve tolerance of pneumoperitoneum, which is a common complication. The purpose of this study was to evaluate the safety and effectiveness of eTEP procedure with placement of polypropylene mesh and fixation by tackers. Method : It was a observational study of 25 cases. The study was conducted in Shaheed Suhrawardy Medical College Hospital, Dhaka from July 2018 to June 2019. Sociodemographic status, operation time, peroperative blood loss, unwanted events like peritoneal tear, vessel injury, nerve injury, duration of hospital stay, postoperative pain and urinary retention were recorded. All the patients were followed up for at least 3 times at the end of 1st week, 1st month and 3rd month. Any surgical site infection, mesh infection, seroma, scrotal swelling, severity of pain according to visual analogue scale, haematoma and recurrence within this time was recorded. All the data were analyzed on SPSS. Result : Among the 25 patients average time of operation was 1 hour and 35 minutes, peroperative blood loss was below 20 ml in all patients, peritoneal tear occurred in 2 patients, 1 vessel injury but no nerve injury was observed during the procedure. One patient had mild chronic pain even after the end of 3rd month. One patient developed scrotal swelling which subsided by the end of 1st week. No SSI, mesh infection, seroma, wound hematoma, and recurrence found within this period. Conclusion : This study showed that, eTEP procedure is cost effective, has minimum complication with easier learning. In the hands of an experienced surgeon, eTEP repair can be safe and effective. New study can be done to find out it’s effectiveness in incisional hernia in lower abdomen and bilateral inguinal hernia. J Shaheed Suhrawardy Med Coll, December 2019, Vol.11(2); 96-100